12-bit ultra-low power low voltage analog to digital converter design for an infrared imaging system - Pang, Bo (2011)
This Final Year Project is to design a 12-bit ultra-low power analog-to-digital converter (ADC). This ADC design is used as part of an on-going NTU research project--development of a Multispectral Infrared Detector Arrays on Read-Out Integrated Circuit (MIDAS-on-ROIC).